Effects of Multisession Anodal Electrical Stimulation of the Auditory Cortex on Temporary Noise-Induced Hearing Loss in the Rat - Díaz, Iván; Colmenárez-Raga, Ana Cecilia; Pérez-González, David; Carmona, Venezia G.; Plaza Lopez, Ignacio; Merchán, Miguel A. (Frontiers in Neuroscience, 2021)
The protective effect of the efferent system against acoustic trauma (AT) has been shown by several experimental approaches, including damage to one ear, sectioning of the olivocochlear bundle (OCB) in the floor of the IV ventricle and knock-in mice overexpressing OHC cholinergic receptors, among others. Such effects have been related to changes in the regulation of the cholinergic efferent system and in cochlear amplification, which ultimately reverse upon protective hearing suppression. In addition to well-known circuits of the brainstem, the descending corticofugal pathway also regulates efferent neurons of the olivary complex. In this paper, we applied our recently developed experimental paradigm of multiple sessions of electrical stimulation (ES) to activate efferent system in combination with noise over stimulation. After 109 dB band noise stimulation for 90 minutes, ABR thresholds shifted 1 and 2 days after AT, recovering at 14 days. However, after multiple sessions of epidural anodal stimulation, no changes in thresholds were observed following AT. Although inflammatory response was also observed 1 day after AT in both groups, the counts of reactive macrophages in both experimental conditions suggest decreased inflammation in the epidural stimulation group. Quantitative immunocytochemistry for choline acetyltransferase (ChAT) showed a significant decrease in the size and optical density of the terminals 1 day after AT and a rebound at 14 days, supporting the depletion of the terminals followed by a long-term compensatory response. Such a synthesis recovery was significantly higher upon cortical stimulation. No significant correlation was found between OD and the size of the buttons in controls and ES/AT +1d animals despite significant negative correlations in all other experimental conditions. The distribution of size and OD values by frequency regions broadened in both experimental conditions, suggesting an underling cochleotopic reorganization. Images of terminals phagocytosis (collateral pruning) by macrophages, together with differences in size along frequencies and time, indicate an active reorganization of the efferent network. Therefore, our comparative analysis suggests that cochleotopic cholinergic neurotransmission is only preserved at AT/ES +1day.